Evaluating the effectiveness of therapy based around Shape Coding to develop the use of regular past tense morphemes in two children with language impairments. (October 2014) - Kulkarni, Amit; Pring, Tim; Ebbels, Susan
It has been suggested that difficulties with tense and agreement marking are a core feature of language impairment. Hence, studies are required that analyse the effectiveness of intervention in this area, including consideration of whether changes seen in therapy sessions generalize to spontaneous speech. This study assessed the effectiveness of therapy based around Shape Coding in developing the use of the regular past tense morpheme -ed in two school-aged children with language impairments. It also considered whether participants benefited from additional generalization therapy in order to start using target forms in their spontaneous speech. The former was assessed using a sentence completion task and the latter by a conversational task with blind assessors. One participant improved markedly in sentence completion but did not gain in the conversation task until after the generalization therapy. The other made more modest gains on the sentence completion task and seemed to generalize to the conversation task without recourse to the generalization therapy. Larger studies are required to confirm these interpretations and to determine whether they are applicable to the wider population of children with language impairments.